Marriage Equality Laws and Youth Mental Health - D. Mark Anderson; Kyutaro Matsuzawa; Joseph J. Sabia (Institute of Labor Economics (IZA), 2019)
Since the landmark ruling in Goodridge v. Department of Public Health in 2004, the legalization of same-sex marriage (SSM) has proliferated throughout the United States via either legislative action or court order. Advocates of SSM laws argue that marriage equality will generate important health benefits not only for adult same-sex couples, but also for LGBQ-identifying youths. Using data from the State Youth Risk Behavior Surveys for the period 1999-2017, we explore the relationship between marriage equality and suicidal behaviors among LGBQ-identifying youths. We find little evidence that SSM laws have reduced suicide attempts among teen sexual minorities, nor have they decreased the likelihood of suicide planning, suicide ideation, or depression. Instead, we find some evidence that SSM legalization via judicial mandate is associated with worse mental health for these individuals.
Keywords: I18; I12; 330; same-sex marriage laws; youth suicide; risky health behaviors